2015
DOI: 10.1016/j.neuroscience.2015.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated TNFα promotes cytokine proteome profile increases and bilateral orofacial hypersensitivity

Abstract: Background: Tumor necrosis factor alpha (TNFα) is increased in patients with headache, neuropathic pain, periodontal and temporomandibular disease. This study and others have utilized TNF receptor 1/2 (TNFR1/2) knockout (KO) animals to investigate the effect of TNFα dysregulation in generation and maintenance of chronic neuropathic pain. The present study determined the impact of TNFα dysregulation in a trigeminal inflammatory compression (TIC) nerve injury model comparing wild-type (WT) and TNFR1/2 KO mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 69 publications
(84 reference statements)
0
19
0
Order By: Relevance
“… 15 , 52 The presence of contralateral sensory deficits have also been reported in various genetic knockout animals, included vasoactive intestinal peptide and tumor necrosis factor alpha receptor knockouts. 18 , 39 Together, these studies suggest that the causes of contralateral effects of nerve injury may stem from multiple mechanisms, and may depend on the type and severity of the injury or disease state.…”
Section: Discussionmentioning
confidence: 97%
“… 15 , 52 The presence of contralateral sensory deficits have also been reported in various genetic knockout animals, included vasoactive intestinal peptide and tumor necrosis factor alpha receptor knockouts. 18 , 39 Together, these studies suggest that the causes of contralateral effects of nerve injury may stem from multiple mechanisms, and may depend on the type and severity of the injury or disease state.…”
Section: Discussionmentioning
confidence: 97%
“…The BDNF binds to its receptor, TrkB, on nociceptive postsynaptic neurons, inducing a shift in the chloride gradient in these cells, which in turn increases their excitability [ 99 , 100 ]. IL-1β, TNF-α and ATP are key mediators, released by activated glial cells, that sensitize neurons [ 18 , 101 ]. IL-1β facilitates N -methyl- d -aspartate receptor phosphorylation on neurons, thereby changing their synaptic strength and resulting in enhanced sensitization of neurons, which leads to behavioral hyperalgesia [ 18 , 84 , 102 ].…”
Section: Mechanisms Of Neuropathic Orofacial Pain: Glial Involvemementioning
confidence: 99%
“…It has been shown that TNFα mRNA and protein are significantly increased in complete Freund’s adjuvant (CFA)-treated TMJ tissues [13, 14] and trigeminal ganglia (TG) [15]. Dysregulated TNFα can promote cytokine proteome profile alteration and orofacial hypersensitivity [16]. TNFα is an inflammatory mediator produced by activated immune cells, glia, and neurons [1719].…”
Section: Introductionmentioning
confidence: 99%